2008
DOI: 10.1103/physrevlett.100.215004
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Density-Gradient Injection of Low Absolute-Momentum-Spread Electron Bunches

Abstract: Plasma density gradients in a gas jet were used to control the wake phase velocity and trapping threshold in a laser wakefield accelerator, producing stable electron bunches with longitudinal and transverse momentum spreads more than ten times lower than in previous experiments (0.17 and 0.02 MeV/c FWHM, respectively) and with central momenta of 0.76 ± 0.02 MeV/c. Transition radiation measurements combined with simulations indicated that the bunches can be used as a wakefield accelerator injector to produce st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
247
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(253 citation statements)
references
References 26 publications
3
247
0
Order By: Relevance
“…Several techniques were also devised in order to control the acceleration processes [16], adjusting the bunch energy, charge [17][18][19][20], and transverse features [21]. Recently, the use of proton drivers was also proposed as a means to accelerate electron beams even further to * 0:5 TeV in & 1 km plasmas [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques were also devised in order to control the acceleration processes [16], adjusting the bunch energy, charge [17][18][19][20], and transverse features [21]. Recently, the use of proton drivers was also proposed as a means to accelerate electron beams even further to * 0:5 TeV in & 1 km plasmas [22].…”
Section: Introductionmentioning
confidence: 99%
“…Electrons from a conventional accelerator can be injected into the wakefield, but matching the beam properties to the wakefield size is difficult leading to low efficiency of particle trapping [32]. A number of advanced techniques have been proposed and demonstrated that use density modification [33][34][35], secondary laser beams [36][37][38] or ionization [39][40][41] to greatly simplify injection into the wakefield. But, perhaps the easiest way of injecting high charge beams into the wakefield is through the use of self-injection [24][25][26].…”
Section: Laser Wakefield Accelerationmentioning
confidence: 99%
“…Recently, acceleration to 1 GeV in a few centimeters was demonstrated [20]. In addition, experiments have shown that the quality of the electron beam can be improved by tailoring the plasma density profile in the injection process separately from the accelerating structure [21,22] or by using colliding laser pulses [23].…”
Section: Introductionmentioning
confidence: 99%